News, Discussion, and Associative Issue Ownership: Instability at the Micro Level versus Stability at the Macro Level. (April 2014) - Kleinnijenhuis, Jan; Walter, Annemarie S.
Associative issue ownership refers to one of the prerequisites for representative democracy—public awareness of the issue priorities of competing political parties. This article addresses the question of how the instability of associative issue ownership at the micro level of individual voters, which could be due in part to election news and political discussion, adds up to the relative stability of associative issue ownership at the macro level. The data come from a panel survey and a content analysis of newspapers and television news bulletins in the 2010 Dutch Parliamentary Election Campaign. Cross-nested multilevel logistic regression models were applied to estimate the impact of political news and political discussion on different respondents for different parties and issues. The findings show how contagion, by traditional issue ownership associations, explains the relative stability at the macro level in spite of volatility at the micro level. Campaign news and political discussion increase the likelihood of contagion by traditional issue priorities of political parties, while also evoking change due to their convergence on the issues of the campaign, from which the parties that own these issues take advantage, among others the VVD and the PVV in the 2010 campaign.